A Proteomic Strategy for Global Analysis of Plant Protein Complexes. Issue 10 (7th October 2014) - Aryal, Uma K.; Xiong, Yi; McBride, Zachary; Kihara, Daisuke; Xie, Jun; Hall, Mark C.; Szymanski, Daniel B.
Abstract : A new size exclusion chromatography and mass spectrometry-based method was developed for proteomic analysis of endogenous protein complexes. It is predicted that about one-third of the detected cytosolic proteins exist in stable oligomeric complexes under optimal growth conditions. The method can be adapted to predict the composition and dynamics of protein complexes under different conditions. Abstract: Global analyses of protein complex assembly, composition, and location are needed to fully understand how cells coordinate diverse metabolic, mechanical, and developmental activities. The most common methods for proteome-wide analysis of protein complexes rely on affinity purification-mass spectrometry or yeast two-hybrid approaches. These methods are time consuming and are not suitable for many plant species that are refractory to transformation or genome-wide cloning of open reading frames. Here, we describe the proof of concept for a method allowing simultaneous global analysis of endogenous protein complexes that begins with intact leaves and combines chromatographic separation of extracts from subcellular fractions with quantitative label-free protein abundance profiling by liquid chromatography-coupled mass spectrometry. Applying this approach to the crude cytosolic fraction of Arabidopsis thaliana leaves using size exclusion chromatography, we identified hundreds of cytosolic proteins that appeared to exist as components of stable protein complexes. The reliability of the method was validated by protein immunoblot analysis and comparisons with published size exclusion chromatography data and the masses of known complexes. The method can be implemented with appropriate instrumentation, is applicable to any biological system, and has the potential to be further developed to characterize the composition of protein complexes and measure the dynamics of protein complex localization and assembly under different conditions.